Varicella zoster virus infections in neurological patients: a clinical study - Thomas Skripuletz (BMC Infectious Diseases, 2018)
Abstract Background Varicella zoster virus (VZV) reactivation is a common infectious disease in neurology and VZV the second most frequent virus detected in encephalitis. This study investigated characteristics of clinical and laboratory features in patients with VZV infection. Methods Two hundred eighty two patients with VZV reactivation that were hospitalized in the department of neurology in the time from 2005 to 2013 were retrospectively evaluated. Results from cerebrospinal fluid (CSF) analysis were available from 85 patients. Results Trigeminal rash was the most common clinical manifestation, followed by segmental rash, CNS infection, facial nerve palsy, postherpetic neuralgia, and radiculitis. MRI of the brain performed in 25/33 patients with encephalitis/meningitis did not show any signs of infection in the brain parenchyma. Only one patient showed contrast enhancement in the hypoglossal nerve. General signs of infection such as fever or elevated CRP values were found in only half of the patients. Furthermore, rash was absent in a quarter of patients with CNS infection and facial nerve palsy, and thus, infection could only be proven by CSF analysis. Although slight inflammatory CSF changes occurred in few patients with isolated rash, the frequency was clearly higher in patients with CNS infection and facial nerve palsy. Conclusion Monosegmental herpes zoster is often uncomplicated and a diagnostic lumbar puncture is not essential. In contrast, CSF analysis is an essential diagnostic tool in patients with skin lesions and cranial nerve or CNS affection. In patients with neuro-psychiatric symptoms and inflammatory CSF changes analysis for VZV should be performed even in the absence of skin lesions.